Public Perception of Corporate Social Responsbility (CSR) at the Hadji Kalla Foundation Through a Netnography Approach - Muhammad Alim BAHRI; Jurana JURANA; Andi Chairil FURQAN; Masrudin MASRUDIN (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to analyze public perception of Corporate Social Responsibility (CSR) programs run by the Hadji Kalla Foundation through a netnography approach. The netnography approach is used to observe public interaction with the Hadji Kalla Foundation's CSR content uploaded through social media and other digital platforms. The research method used is descriptive qualitative with data collection through digital observation and analysis of netizen comments on CSR-related content. The results of the study indicate that public perception of the Hadji Kalla Foundation's CSR programs is very positive, especially in the fields of education, health, economic empowerment, and social assistance. Most of the community interactions are in the form of comments expressing gratitude, appreciation, and high interest in the programs being run. In addition, this study found that the use of social media as a means of CSR communication has an important role in building a positive image of the foundation. Based on these findings, the Hadji Kalla Foundation is advised to continue developing CSR programs that focus on community empowerment and strengthening digital communication to increase community involvement.